Religious Moderation, Academic Reform, and Global Competitiveness in Indonesian Islamic Higher Education - Aminullah, Aceng; Nurdiyansah, Riyan; Hernandi, Hernandi (Jurnal Penelitian Pendidikan Islam, 2026)
This article examines the relationship among religious moderation, academic reform, and global competitiveness in Indonesian Islamic higher education. Using a qualitative literature-based approach, more specifically an integrative literature review, the article synthesizes recent studies on moderation policies, curriculum integration, institutional governance, pedagogical innovation, digital transformation, internationalization, and Islamic identity. The analysis shows that religious moderation functions as an ethical foundation for strengthening tolerance, balance, justice, national commitment, and cultural accommodation within Islamic universities. Academic reform provides the institutional mechanism through which these values are translated into curriculum, pedagogy, research, quality assurance, and digital innovation. Global competitiveness, meanwhile, creates strategic pressure for Islamic higher education to improve international visibility, institutional performance, research productivity, and technological capacity. However, the article also finds that these agendas may produce tensions, particularly when moderation remains superficial, academic reform imitates secular models uncritically, or global competitiveness is driven mainly by rankings and academic capitalism. The article contributes by offering an integrated framework for understanding Indonesian Islamic higher education as a negotiated field in which Islamic values, institutional reform, and global academic pressures shape one another.